Relationships of Behavioral, Cognitive, and Decisional Control in Self Control of Deaf Student - Mirasandi, Istiqomah Putri (The Center for Disability Studies and Services Brawijaya University, 2019)
This study aims to determine the relationship between behavioral control, cognitive control, and decisional control in self-control in children with hearing impairments. The sample of this research is the students of Junior High School and Senior High School in Special School X Surakarta section of Hearing Impairment, totaling 30 students. Data collection techniques in this study using questionnaire instrument in the form of Likert scale. This research uses quantitative research method with descriptive statistical analysis. The results showed that children's self-control with hearing impairments was highest in the aspect of decisional control, then behavioral control, and the lowest was cognitive control.